Spartina alterniflora modifies the native arbuscular mycorrhizal fungal community in coastal ecosystem - Jiang, Yuxin; Li, Meng; Guo, Xiaohong (Frontiers in Microbiology, 2025)
The effect of invasive plants is mediated by their interactions with microbial communities. However, it is still uncertain how Spartina alterniflora impacts the arbuscular mycorrhizal fungi (AMF) community within the native rhizosphere what the resulting AMF differences are associated with. Here, we investigated what kind of AMF communities are formed in the roots of S. alterniflora to distinguish it from native plants such as Suaeda salsa, Phragmites australis, and Tamarix chinensis by analyzing the AMF communities and the associations with selected environmental factors. The dynamics of AM fungal communities are linked to plant-soil systems. The AMF communities of S. alterniflora and native vegetation demonstrated notable differences in composition, diversity, and symbiotic networks. Significantly higher ω, Ec, AN, AP, and AK were observed in S. alterniflora-invaded soils. Although plant rhizosphere AMF responded to soil environmental factors, AN and AP were highly explanatory environmental factors driving AMF community characteristics during S. alterniflora expansion, while increased soil P and N availability may be involved in shaping AMF community characteristics in S. alterniflora. Our findings can provide complementary evidence-based solutions for defending against invasive plants and mitigating their impacts, as well as protecting coastal ecosystems.